Introduction to the EC’s Marie Curie Initial Training Network Project: The European Training Network in Digital Medical Imaging for Radiotherapy (ENTERVISION) - Dosanjh, Manjit; Cirilli, Manuela; Navin, Sparsh (Frontiers in Oncology, 2015)
Between 2011 and 2015, the ENTERVISION Marie Curie Initial Training Network has been training 15 young researchers coming from a variety of backgrounds on topics ranging from in-beam Positron Emission Tomography or Single Particle Tomography techniques, to adaptive treatment planning, optical imaging, Monte Carlo simulations, biological phantom design. This article covers the main research activities, as well as the training scheme implemented by the participating institutes, which included academia, research, and industry.